The Implementation of Progressive Approach in Learning Reading Course by the Third Year Students of Sumatera University (Pseudonym) - Erni, Erni (Proceedings of the 1st UR International Conference on Educational Sciences, 2017)
This is a case study research design. The purposes of the study are to explore the studentsâ learning reading activities taught through progressive approach and the classroom environment in learning reading at the University of Sumatera. There were 20 students involved as the participants of this study. The data were collected through field note, observation, and interview for a triangulation method. This triangulation was done to ensure validity and reliability of the data. The data analysis technique answered the research question of the study. The findings of this study illustrated that the students read text individually and discussed with peer. They also discussed difficult materials with lecturer and then share ideas to friends. In addition, the students showed creative reading where they did independent reading even though the lecturer did not encourage further extensive reading. In general, the findings indicated that the progressive approach was implemented by students in their reading activities in learning reading III course and classroom environments were conducive at the beginning and while learning process. However, a number of activities and classroom environment still did not encourage the implementation of progressive approach and these have contributed to the studentsâ reading comprehension problem. This impies that the implementation of progressive approach can increase studentsâ reading activities and participation in learning reading course but not for the reading comprehension achievement. There is a need to be improved and to ensure that students comprehend well of what they read and thus improve their reading ability.